2015
DOI: 10.4103/0973-029x.157193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fungal hyphae in potentially malignant lesions and conditions-does its occurrence play a role in epithelial dysplasia?

Abstract: Background:Oral cancer is a major public health problem in India. A key factor that has led to lack of improvement in prognosis of oral cancer over the years, is delay in diagnosis and treatment. In many instances, a significant proportion of oral squamous cell carcinomas develop from premalignant lesions and conditions. Identification of such lesions and conditions is very important in order to prevent malignant transformation. The role of fungal infections has been studied and holds promise as an indicator t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
1
20
0
1
Order By: Relevance
“…In the present study, the presence of Candida in SDA medium showed maximum specimens from OSCC followed by PMD and least in controls. Similarly, the results were demonstrated by various investigators such as Hongal et al .,[12] Saigal et al .,[1] Anila et al . [25] and Vučković et al .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, the presence of Candida in SDA medium showed maximum specimens from OSCC followed by PMD and least in controls. Similarly, the results were demonstrated by various investigators such as Hongal et al .,[12] Saigal et al .,[1] Anila et al . [25] and Vučković et al .…”
Section: Discussionsupporting
confidence: 82%
“…Few investigators have also indicated that the presence of candidal infection increases the risk of malignant transformation in premalignant lesions. [12] Yeasts are common commensal organisms found in approximately 40% of individuals, the predominant species isolated being C. albicans . C. albicans predominantly affects oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] These findings propound a convincing association between leukoplakia and Candida species which was first reported in 1965 by Cernea et al, and Jepsen and Winther. [22] Colonization of Candida species in oral leukoplakia was studied by Sarkar et al by employing direct microscopy and histopathological diagnostic methods to ascertain the statistical correlation between candidal invasion and epithelial dysplasia. Year Types of Candida species Daftary et al [13] 1972 Candida albicans Krogh [14] 1990 Candida albicans, Candida tropicalis, Candida parapsilosis…”
Section: Candida Species In Opmdsmentioning
confidence: 99%
“…For example, the prevalence of Candida infection in OLK, erosive OLP, and OSF is 47%, 44.29%, and 36.67%, respectively [ 33 35 ]. Other infections may be associated with OPMD such as Helicobacter pylori [ 36 ], HCV [ 37 ], and fungal hyphae [ 38 ], and the infection rate is about 90% [ 36 ], 23% [ 37 ], and over 25% [ 38 ], respectively.…”
Section: Introductionmentioning
confidence: 99%